Development of a stacked wire-mesh structure for diesel soot combustion - Banus, Ezequiel David (2014)
This work describes the development of stacked wire-mesh structures and their washcoating method to prepare a structured system for the catalytic combustion of soot. For this purpose, a metallic structured substrate was designed and built using wire-mesh discs of AISI 304. The coating of this substrate was optimized by investigating various strategies and parameters of the washcoating such as the suspension formulation (sol–gel coating with posterior impregnation of the active phase, the all-in-one strategy using catalyst precursors and the preparation of the catalyst slurry with a ready-made catalyst), the amount of Co, Ba, K/CeO2 catalyst and the packing material (wire diameter and number of packed discs). The coating proposed strategies were analyzed measuring textural properties, catalyst coating adherence and morphology, and pressure drop of the catalytic substrate. Finally, the coated wire-mesh substrates were tested in the combustion of soot showing promising catalytic activity.